Prevalence of bacterial vaginosis in Portuguese pregnant women and vaginal colonization by Gardnerella vaginalis - Machado, Daniela (2017)
Supplemental information for this article can be found online at: http://dx.doi.org/10.7717/ peerj.3750#supplemental-information.